High stability and visible-light photocatalysis in novel two-dimensional monolayer silicon and germanium mononitride semiconductors: first-principles study. Issue 24 (8th April 2020) - Zhang, Kaining; Li, Nan
Abstract : The two-dimensional SiN and GeN semiconductors are expected to become novel photocatalysts for water-splitting. Abstract : Recently, two-dimensional semiconductor materials with moderate band gaps and significant light absorption have been highly sought for application in photocatalysis and nanoelectronics. In this study, novel monolayer SiN and GeN have been predicted by using first-principles calculations. They have excellent thermal and dynamic stabilities and present indirect band gaps of 2.58 eV and 2.21 eV with anisotropic carrier mobility, respectively. Suitable band gaps and band edges of SiN and GeN indicate that they can simultaneously produce both hydrogen and oxygen in the pH range of 6 to 14 and 0 to 10, respectively. Theoretical studies on strain engineering show that their band gaps could be effectively tuned by both biaxial tensile and compressive strain. Our work enriches the family of two-dimensional semiconductor materials and shows that monolayer SiN and GeN are promising candidates for electronic devices and photocatalysis.